American education - Spring, Joel H.; 1965- (New York McGraw-Hill, 2012)
"Clear, concise, and authoritative compact and affordable, too with scholarship that is often cited as a primary source, American Education brings up-to-date information and challenging perspectives to teacher educators' classrooms. Revised every two years, American Education provides a fresh, concise, and up-to-date introduction to the historical, political, social, and legal foundations of education and to the profession of teaching in the United States"-- |c Provided by publisher.
Keywords: Education -- Social aspects -- United States; Education -- Political aspects -- United States; Educational equalization -- United States; Education and state -- United States; Giáo dục Hoa Kỳ